Determination of the Cabibbo–Kobayashi–Maskawa matrix element |Vcb|. (23rd September 2020) - Ricciardi, Giulia; Rotondo, Marcello
Abstract: In this review we present and discuss the determination of the magnitude of the Cabibbo–Kobayashi–Maskawa (CKM) matrix parameter V cb . The CKM matrix parametrizes the weak charged current interactions of quarks in the standard model (SM), and a precise determination of its elements has always been one of the most important targets of particle physics. The precise knowledge of the | V cb | value plays a pivotal role in testing the flavour sector of the SM and in the analyses of the unitarity of the CKM matrix. The SM does not predict the values of the CKM matrix elements, which have to be extracted by experimental data. Given the variety of channels that allow the extraction of | V cb |, different theoretical and experimental techniques are mustered for the | V cb | determination. The exertion towards precision represents not only a significant test of our theoretical procedures but a stimulus towards better detection performances. The most precise measurements of | V cb | come from semileptonic decays, that being tree level at the lowest order in the SM are generally considered unaffected by physics beyond the SM. After summarizing the characteristics of the SM that set the frame for the determination of | V cb |, we discuss inclusive and exclusive semileptonic B decays. We analyse the | V cb | extraction methods and recent results, detailing both the theoretical and experimental techniques, and, finally, outline future prospects. We also comment on exclusive decays into heavy leptons, on the observables R ( D ) and R ( D * ), on decays to excited D meson states and on baryon decays.